Aneurysmal Bone Cyst Presenting with Neurological Deficit: Two Cases Reports and Review of the Literature - Matheus Felipe Henriques Brandão; Talita Helena Martins Sarti; José Lopes Sousa Filho; Maurus Marques de Holanda Almeida; Gustavo Victor Neves Porto; Juliete Melo Diniz; Daniel de Araújo Paz (Brazilian Neurosurgery, 2025)
Aneurysmal bone cysts are rare, benign, hypervascular lesions, locally destructive due to their progressive growth. The severity of symptoms depends on the degree of associated spinal cord injury. The surgical approach is the main treatment method and aims at complete tumor resection with reconstruction and/or stabilization of the spine. The goal of this study is to present the authors' experience with surgical treatment of aneurysmal bone cysts of the thoracolumbar spine in the pediatric population and describe the treatment in the context of literature. Two patients of the authors and reports in the literature were identified and analyzed. A 16-year-old female presented with acute spinal cord syndrome classified as ASIA A due to thoracic cord compression. The second patient is an 8-year-old male admitted with left leg weakness due to compression of lumbar roots. Both patients underwent complete tumor resection with corpectomy, reconstruction of the anterior spine with body cage, and stabilization of the posterior spine with pedicular screws. After 6 months of surgery, they evolved with significant improvement in motor strength. Even at severe clinical presentation, the patient with an aneurysmal bone cyst may improve neurological deficits if treated in a timely manner, with tumor resection, spinal cord and/or nerve decompression, spinal reconstruction, and postoperative rehabilitation.